Fritillaria thunbergii Miq. (Zhe Beimu): A review on its traditional uses, phytochemical profile and pharmacological properties. (July 2021) - Nile, Shivraj Hariram; Su, Jiajia; Wu, Die; Wang, Leran; Hu, Jiangning; Sieniawska, Elwira; Kai, Guoyin
Abstract: Fritillaria thunbergii Miq. (Zhe beimu) ranked as oldest known homeopathic traditional folk medicine in China. The bulbs are medicinally important curing cough, inflammation, gastric ulcers, hypertension, diarrhea, and bronchitis. The aim of this review is to enlighten the deeper knowledge about F. thunbergii giving a comprehensive overview on its traditional uses, phytochemistry and pharmacology for future investigation of plant-based drugs and therapeutic applications. Total 48 medicinally important species of Fritillaria were described; total 122 compounds have been identified as results only 72 chemical constituents were described with proper chemical and biological details. F. thunbergii and its bulbs mainly constitute alkaloids, essential oils, diterpenoids, carbohydrates, sterols, amino acids, nucleosides, fatty acids, and lignans. The pharmacological studies demonstrate that F. thunbergii and its bulbs displays a wide range of bioactivities e.g., anti-inflammatory, anticancer, antitussive, expectorant, anti-ulcer, antimicrobial, antioxidant, anti-thyroid, regulation of blood rheology, anti-diarrhea, neuroprotection, and analgesic effects. Although promising reports on the various chemical bioactive constituents and biological properties of F. thunbergii have been published, very few reviews are related specifically to the traditional uses, phytochemistry and pharmacological applications. Further, various other studies on these plants should deserve our more attention for future investigation for drug development and its therapeutic applications. Graphical abstract: Image 1 Highlights: F. thunbergii Miq. (Zhe beimu) oldest known homeopathic plant of TCM. Discussed phytochemicals, traditional and pharmacological properties. 122 compounds identified, 72 described with chemical and biological details. F. thunbergii and its bulbs displays a wide range of bioactivities.